Test control of knowledge and his analysis on the example of environment for learning course of «Basics of Algorithmization and programming» (Journal of Information Technologies in Education (ITE), 2009)
The article examines possibilities of text control in providing of optimization of educational process as an effective mean of activation of educational activity of students at the learning course of «Basics of algorithmization and programming».
Keywords: algorithmic tests; current and final control of knowledge; tests; types of answers